To analyze the effects of leucine-rich alpha-2 glycoprotein-1 (LRG1) on angiogenesis in diabetes associated ischemic heart disease - Lee, Charmaine Zhi Ning (2017)
The incidence of ischemic heart disease (IHD) is rising globally. Current treatment strategies do not alter the underlying process or the natural progression of the disease. Furthermore, not all patients can undergo treatment or benefit from it because of their multiple comorbidities, such as diabetes. It has been shown that diabetic patients have an increased risk of having cardiovascular diseases. Therapeutic angiogenesis is a potential area for intervention in IHD. Current studies have shown promising results using angiogenic proteins such as vascular endothelial growth factor (VEGF) for treatment. However, it is limited by the formation of unstable vessels. LRG1 is a novel angiogenic factor, thought to promote angiogenesis by modulating the TGFβ signaling pathway thus exerting effects in the different stages of vessel development. In this study, the role of LRG1 KO in diabetes associated IHD on angiogenesis and fibrosis was analyzed. Results showed decreased expression of angiogenic markers and increased expression of fibrotic markers in LRG1 KO compared to wild type mice. However, the role of LRG1 KO on diabetes associated IHD is inconclusive, limited by the sample size. Therefore, this study suggests that LRG1 is a potentially useful target to treat IHD.